Analysis of ineffective breathing pattern and impaired spontaneous ventilation of adults with oxygen therapy - Deborah Hein Seganfredo; Beatriz Amorim Beltrão; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes; Stela Maris de Jezus Castro; Miriam de Abreu Almeida (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze the manifestation of the defining characteristics of the nursing diagnoses of ineffective breathing pattern and impaired spontaneous ventilation, of the NANDA International and the defining characteristics identified in the literature for the concept of "ventilation" in adult patients hospitalized in an intensive care unit with use of oxygen therapy. Method: clinical diagnostic validation study, conducted with 626 patients in intensive care using oxygen therapy, in three different modalities. Multiple correspondence analysis was used to verify the discriminative capacity of the defining characteristics and latent class analysis to determine the diagnostic accuracy of them, based on the severity level defined by the ventilatory mode used. Results: in the multiple correspondence analysis, it was demonstrated that the majority of the defining characteristics presented low discriminative capacity and low percentage of explained variance for the two dimensions (diagnoses). Latent class models, separately adjusted for the two diagnoses, presented a worse fit, with sharing of some defining characteristics. Models adjusted by level of severity (ventilation mode) presented better fit and structure of the component defining characteristics. Conclusion: clinical evidence obtained in the present study seems to demonstrate that the set of defining characteristics of the two nursing diagnoses studied fit better in a single construct.